PENGARUH KEMAMPUAN KERJA, MOTIVASI KERJA, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN KABUPATEN BARITO SELATAN - Nilawati (KINDAI, 2021)
Abstract: This research is to analyze the influence, motivation, opportunities, and partial participation on employee performance in the Dinas Pendidikan Kabupaten Barito Selatan. The object of research was employees at the Dinas Pendidikan Kabupaten Barito Selatan. A total of 500 employees. Determination of the sample in this study using simple random sampling, with a sample of 10% of the total sample used for as many as 50 respondents. The independent variables in this study are ability, motivation, opportunity, and discipline, while the required variable is employee work performance. The analysis technique used is multiple linear regression analysis. Transformed regression shows all regression coefficients that are positive, which means all expected independent variables in the model have a direction of change in the direction of the added variables, meaning that the independent variable rises assuming the other independent variables remain free so that the variable rises as well. Based on the analysis results it is concluded that the independent variables collected have a significant effect on the dependent variable. This can be assessed from the results of the t statistical calculation, the t value is greater than t table. The results showed that: Ability (X1) influences employee performance (Y) with a t value of 5.313 greater than t table of 1.701 with a significance level of 0,000. Motivation (X2) affects employee performance (Y) with a t value of 2.780 greater than t table of 1.701 with a significance level of 0.007. Opportunity (X3) influences employee performance (Y) with a t value of 2.116 greater than t table of 1.701 with a significant degree of 0.038. Discipline (X4) has an effect on employee performance (Y) with a t value of 3.922 greater than t table of 1.701 with a significant degree of 0,000. The conversion coefficient is Multiple R of 0.512, this shows that there is a strong relationship between independent variables consisting of ability (X1), motivation (X2), opportunity (X3), and discipline (X4) together to support the achievement employment at Dinas Pendidikan Kabupaten Barito Selatan. This relationship is categorized as strong because of the value Keyword: Employee's Ability, Motivation, Opportunity, Discipline, and Work Performance.